2014
DOI: 10.1152/ajpendo.00487.2013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aerobic exercise intensity on myofibrillar and mitochondrial protein synthesis in young men during early and late postexercise recovery

Abstract: Di Donato DM, West DW, Churchward-Venne TA, Breen L, Baker SK, Phillips SM. Influence of aerobic exercise intensity on myofibrillar and mitochondrial protein synthesis in young men during early and late postexercise recovery. Am J Physiol Endocrinol Metab 306: E1025-E1032, 2014. First published March 3, 2014 doi:10.1152/ajpendo.00487.2013.-Aerobic exercise is typically associated with expansion of the mitochondrial protein pool and improvements in muscle oxidative capacity. The impact of aerobic exercise inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 36 publications
8
104
6
Order By: Relevance
“…The HIT protocol was particularly effective for increasing mTOR and rps6 phosphorylation compared with MICT, whereas both protocols similarly increased p70S6K phosphorylation at POST. These data align with evidence that endurance exercise is sufficient to induce anabolic responses in skeletal muscle, including increased mTORC1 signaling and rates of MPS, at least in relatively training-unaccustomed individuals (28,61). For example, mTOR/p70S6K phosphorylation and rates of mixed MPS are increased following 1 h of cycling at 65-70% V O 2 max (61), and high (60% W max for 30 min)-but not low (30% W max for 60 min)-intensity continuous cycling induces sustained (24 -28 h postexercise) increases in myofibrillar MPS (28).…”
Section: Discussionsupporting
confidence: 84%
“…The HIT protocol was particularly effective for increasing mTOR and rps6 phosphorylation compared with MICT, whereas both protocols similarly increased p70S6K phosphorylation at POST. These data align with evidence that endurance exercise is sufficient to induce anabolic responses in skeletal muscle, including increased mTORC1 signaling and rates of MPS, at least in relatively training-unaccustomed individuals (28,61). For example, mTOR/p70S6K phosphorylation and rates of mixed MPS are increased following 1 h of cycling at 65-70% V O 2 max (61), and high (60% W max for 30 min)-but not low (30% W max for 60 min)-intensity continuous cycling induces sustained (24 -28 h postexercise) increases in myofibrillar MPS (28).…”
Section: Discussionsupporting
confidence: 84%
“…In a number of studies, activation of AMPK (Rasmussen & Winder 1997, Fujii et al 2000, Chen et al 2003, Sriwijitkamol et al 2007, Egan et al 2010, CaMKII (Rose et al 2006, Egan et al 2010, and stress-inducible p38 MAPK (Di Donato et al 2014) positively associated with the intensity of exercise were shown in human skeletal muscle, while in one study (Egan et al 2010) such association for p38 MAPK was not observed. We found that in endurance-trained human skeletal muscle, the canonical promoter PGC-1a is constitutively expressed at rest and after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that the increased myofibrillar protein synthetic response to endurance exercise and amino acid ingestion may be the result of a delayed temporal response (i.e. 24-28 h post-exercise) of mitochondrial proteins to endurance exercise (Di Donato et al, 2014). Moreover, in addition to the previously mentioned increase in myosin heavy chain I, protein ingestion with chronic endurance programmes may be required to cause a shift toward mitochondrial-specific responses (Wilkinson et al, 2008).…”
Section: Reduced Energy Availabilitymentioning
confidence: 99%